Nonoliguric hyperkalemia in a late preterm infant with severe birth asphyxia - Xiong, Xiaoyu; Chen, Dan; Zhang, Jing; Mao, Jian; Li, Juan (Translational Pediatrics; Vol 2, No 1 (January 06, 2013): Translational Pediatrics, 2013)
Nonoliguric hyperkalemia (NOHK) is common during the first days after birth in premature infants with gestational age